PENGARUH KEPUASAN KERJA DAN PERILAKU KEPEMIMPINANTERHADAP KOMITMEN KARYAWAN - CHUSNIA SN, CHAULA (Jurnal Ilmu Manajemen (JIM), 2013)
Organization requires human resources who areCompetent, it is anticipated any change whitin the organization, bothinternal and external environment. Common problems related to theemployee’s job in general is the lack of commitment and satisfactionof one’s importance and the role of leadership to realize thecompany’s performance. The population used in this study is thecompany PT. Tri Ratna Diesel Indonesia has 97 employees ofproduction section which is used as in this study population. Theanalysis method used is the technique of test validity, Reliability test,Testing Assumptions Classical (Multicollinearity Test, TestHeterokedastisitas,Autocorrelation and Normality Test), multiple linearregression analysis, the coefficient of determination, and hypothesistesting. From this study it can be concluded simultaneously no effectbetween job satisfaction and Leadership Behavior on EmployeeCommitment. Partially Job Satisfaction an Leadership Behavior effecton Employee Commitment. The most dominant factor influenced thevariable salary.Keywords: job satisfaction, leadership behavior and employee commitment.